Tensile strength and elongation of selected Kenaf fibres of Ghana. Issue 1 (31st December 2023) - Ansong, George; Fiagbe, Yesuenyeagbe A.K.; Tetteh, Antonia Y.; Davis, Francis
Abstract: There are a number of genotypes/varieties of kenaf (Hibiscus cannabinus L) fibre in Ghana. The kenaf fibre is used in both engineering and social products and its properties improve its choice. This paper reports the tensile strength and elongation of five genotypes of the kenaf fibre in Ghana. The fibres are cultivated and harvested at maturity and prepared with water retting. A gauge length of 20 mm was used and cardboard as the initial support. The fibre diameters are found for each genotype to be 34.2 µm, 40.4 µm, 38.2 µm, 43.2 µm and 39.2 µm for EB31, TN11, EN31, PN11 and HN11 respectively. The densities are 0.53 g/cm 3 for EB31; 0.60 g/cm 3 for TN11; 0.63 g/cm 3 for EN31; 0.94 g/cm 3 for PN11 and 1.00 g/cm3 for HN11. The tensile strengths are 734.53 MPa for EB31, 1292.37 MPa for TN11, 1241.53 MPa for EN31, 979.35 MPa for PN11 and 1365.14 MPa for HN11. The corresponding percentage elongations are found to be 10.88 for EB31; 12.23 for TN11; 14.66 for EN31; 15.81 for PN11 and 13.13 for HN11. These results will make the application of fibre in various engineering applications, especially in composites, more predictive in properties and performance.